2019
DOI: 10.1136/bmjpo-2019-000491
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes of very low birthweight infants born to mothers with hyperglycaemia in pregnancy: a retrospective cohort study in Japan

Abstract: ObjectiveTo examine the mortality and morbidities of very low birthweight (VLBW, <1500 g) infants of mothers with hyperglycaemia in pregnancy.Design and settingWe conducted a retrospective cohort study using data from the Neonatal Research Network of Japan, a nationwide registry of VLBW infants (2003–2012).PatientsWe studied 29 626 infants born at 23 to 32 weeks without major congenital anomalies, of which 682 (2.3%) infants were from pregnancies affected by maternal hyperglycaemia.Main outcome measuresThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Hitaka et al evaluated very low birth weight (VLBW) (<1500 gr) infants in Japan and showed that mortality and morbidity were not significantly different between infants of mothers with or without hyperglycinemia in pregnancy [ 189 ]. When 682 infants of mothers with hyperglycemia were compared to 28,944 infants of normoglycemic mothers, there was no statistical difference in the rate of necrotizing enterocolitis (NEC) ( p = 0.67), patent ductus arteriosus (PDA) ( p = 0.52), severe intraventricular hemorrhage (IVH), or periventricular leukomalacia (PVL) ( p = 0.27) and retinopathy of prematurity (ROP) ( p = 0.27).…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
See 2 more Smart Citations
“…Hitaka et al evaluated very low birth weight (VLBW) (<1500 gr) infants in Japan and showed that mortality and morbidity were not significantly different between infants of mothers with or without hyperglycinemia in pregnancy [ 189 ]. When 682 infants of mothers with hyperglycemia were compared to 28,944 infants of normoglycemic mothers, there was no statistical difference in the rate of necrotizing enterocolitis (NEC) ( p = 0.67), patent ductus arteriosus (PDA) ( p = 0.52), severe intraventricular hemorrhage (IVH), or periventricular leukomalacia (PVL) ( p = 0.27) and retinopathy of prematurity (ROP) ( p = 0.27).…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
“…In the year 2010, the criteria for hyperglycemia were changed so that the frequency of GDM pregnancies increased twofold to fourfold to 6–12%. The increased risk of RDS observed only in infants of mothers with hyperglycemia in pregnancy diagnosed before the relaxation of the GDM diagnostic criteria reflects the severity of maternal hyperglycemia in that time period [ 189 ]. Grandi et al evaluated the outcome of VLBW infants of diabetic mothers (both GDM and PGDM) from the NEOCOSUR South American Network (Argentina, Brazil, Chile, Paraguay, Peru, and Uruguay) [ 190 ].…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have reported maternal DM as a risk factor for ROP development [ 236 , 237 , 238 ], while others claimed no relationship [ 239 , 240 , 241 ]. One recent meta-analysis showed no association between maternal DM and ROP [ 242 ], but the heterogeneity among studies in terms of baseline subject characteristics and diabetes management may be overlooked.…”
Section: Correlation With Other Maternal or Neonatal Diseasesmentioning
confidence: 99%
“…This process ensures the database is up-to-date and, therefore, useful for neonatal research studies. [7][8][9][10][11][12][13][14] We used data on VLBW infants born between January 2003 and December 2012, mainly from level-3 perinatal centers that were documented in the NRNJ database (N = 40,806). The list of 204 participating centers has already been published.…”
Section: Subjects and Datasetmentioning
confidence: 99%